1997
DOI: 10.1159/000121219
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Axial Tumors of the Cervicomedullary Junction: Surgical Results and Long-Term Outcome

Abstract: Until recently, intra-axial brainstem tumors were traditionally regarded as surgically inaccessible lesions with a uniformly poor prognosis. However, increasing data indicate that distinct subgroups of brainstem tumors exist that are amenable to surgical intervention. To address this question, we reviewed our experience in the operative management of 39 consecutive patients, in the magnetic resonance imaging (MRI) era, with intra-axial cervicomedullary tumors, in order to determine those factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 21 publications
(33 reference statements)
2
37
0
Order By: Relevance
“…Furthermore, treatment delay to time of progression (median 1.21 years, range 0.05-13.95) conferred no survival disadvantage for these patients. In agreement with our results, Weiner et al [22] reported PFS and OS of 60% and 89% in 39 patients with partially resected cervicomedullary lesions with varied pathologies undergoing observation. Similar outcomes were reported by other authors [23,24].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, treatment delay to time of progression (median 1.21 years, range 0.05-13.95) conferred no survival disadvantage for these patients. In agreement with our results, Weiner et al [22] reported PFS and OS of 60% and 89% in 39 patients with partially resected cervicomedullary lesions with varied pathologies undergoing observation. Similar outcomes were reported by other authors [23,24].…”
Section: Discussionsupporting
confidence: 93%
“…If a fundamentally important article was missed in the initial search, it would surely be encountered in the reference lists of the reviewed papers and as such would be cited extensively. In fact, articles not found on Medline were discovered by this strategy [19,48,72] and neither proved to substantially influence the resulting review. Any newly published article is today most likely to appear on Medline, we used the ''What's new'' function to ascertain that no such article [46] escaped our attention.…”
Section: Discussionmentioning
confidence: 99%
“…4,16,33,38,42 Cervicomedullary tumors are a rare group of diverse tumors. The majority of patients have low-grade tumors with long duration of preoperative symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…20 Some believe that resection should be the treatment of choice for CMTs. 4,16,24,38,40 Patients with longer prodrome and less severe neurological deficits prior to resection typically have the lowest risk of sustaining a significant neurological deficit after surgery, and in general have a favorable overall survival prognosis. 1,14,33,38 However, depending on the tumor pathological and radiographic characteristics, radiotherapy (RT) and/or chemotherapy may supplement or be considered a better primary treatment than surgery.…”
Section: 2332mentioning
confidence: 99%